Pengaruh CEO Narsisme dan Ukuran Perusahaan terhadap Kinerja Keuangan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) - Rahmi, Fitri; Arza, Fefri Indra (Jurnal Nuansa Karya Akuntansi, 2024)
This exploration expects to decide the impact of CEO self-absorption and company size on monetary execution in assembling organizations recorded on the Indonesian Stock. This examination utilizes an quantitative methodology. in this examination is193 organizations that are recorded on the Indonesia Stock Trade and have distributed reports for the 2020-2022 period. The examination procedure utilized purposive testing with an example size of 30 organizations. The sort of information utilized in this exploration is auxilliary information. Information examination utilizes the Numerous Straight Relapse Test. In view of the exploration results, it is reasoned that self-centeredness adversely fundamentally affects monetary execution. Than organization size as proxied by Ln All out resources undamentally affect monetary. Basides, Chief self and company size as proxied by Ln complete resources all the while altogether affect monetary execution. The coefficient of assurance test results seen from the changed R square worth are 0.064, this means 6.4% of the recorded on the Indonesian Stock Trade (BEI) which can be made sense of by Chief self-absorptiona nd company size which is proxied by Ln absolute resources while the leftover 93,6% is made sense of bye different variables not analyzed in this review.